Effectiveness of rice husk in the removal of methyl orange dye in Constructed Wetland-Microbial Fuel Cell. (December 2022) - Sonu, Kumar; Sogani, Monika; Syed, Zainab; Rajvanshi, Jayana; Sengupta, Nishan
Abstract: Research has established that biological processes are more suited for synthetic dyes wastewater treatment than physical and chemical methods. In the present study, a cellulose-based agricultural waste such as rice husk was employed as a substratum in a Constructed Wetland-Microbial Fuel Cells (CW-MFCs) system employing two integrated units one with the down-flow and one with the up-flow system. The study was performed on two levels to assess the efficacy of each process: dye adsorption on the substratum and phytoremediation within the CW-MFC. The adsorption procedure was effective in removing 68 % of the dye in the presence of rice husk. The addition of rice husk to the CW-MFC system increased the dye removal efficiency up to 98 %, COD removal by 85.29 %, with a maximum power density of 102.08 mW/m 2 . Overall, the results indicate that using rice husk as a supplement in the CW-MFC system may provide effective applications in wastewater treatment. Graphical abstract: Unlabelled Image Highlights: Eco-friendly and cost-effective wastewater treatment using an agricultural waste Development of an up-flow and down-flow Constructed Wetland-Microbial Fuel Cell Rice husk enhanced the decolorization of methyl orange wastewater up to 98 %. Lagergren's pseudo-II order kinetic model was the best fit for the chemisorption.